BEADS GTAW ON LEAN DUPLEX STAINLESS STEEL SHEETS (Journal of Industrial and Mechanical Engineering, 2020)
In this work we studied the effect of the heat input in GTAW welds, from simple beads on lean duplex sheets (bead on plate), on the geometric characteristics of the bead, the microstructural balance and hardness.For this purpose, welding coupons with different heats input (0.3 to 1.9 kJ / mm) were welded on lean duplex sheets.The width, penetration and area of the weld metal were measured, the microstructure was characterized by light andscanning electron microscopy, the austenite content was quantified and the average grain size was measured by image analysis software.In addition, microhardness Vickers with 1 kg load was measured.It was observed that the heat input has a great influence on the microstructural behavior of the weld metal.This influence controls hardness. Expressions were obtained that relate the heat supplied with the different characteristics determined in this work.
Keywords: Lean Duplex Stainless Steel; Heat Input; Microstructural Balance; Microhardness; Localized Corrosion Resistance